2012
DOI: 10.3354/meps09803
|View full text |Cite
|
Sign up to set email alerts
|

Mate selection in captive-breeding rockfishes Sebastes spp.: inference from parentage analysis and the major histocompatibility complex (MHC)

Abstract: Rockfish species of the genus Sebastes are notable for being numerous and diverse. Rockfishes are unusual among fish because they fertilize their eggs internally and release live, swimming larvae. They undergo complex courting behaviors, which may allow females to be selective about their mates. The major histocompatibility complex (MHC) is implicated as having an important influence on mate selection in other fishes, especially in sticklebacks and salmonids. Research suggests that females choose mates that op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…In some mammals, the female reproductive tract can recognize and interpret spermatozoon's genetic signature (Holt & Fazeli, 2015); nonetheless, it is unknown if rockfishes have the capability for distinguishing among sperm and for biased use of stored sperm. In some rockfishes ( Sebastes alutus , S. atrovirens , Sebastes caurinus , Sebastes maliger and S. schlegelii ), the distribution of fertilization success among males was observed to be skewed, which could point to potential post‐copulatory selection, disproportionate quantity of sperm from different males or study sampling effects (Gao et al ., 2017; Johansson et al ., 2012; Sogard, Gilbert‐Horvath, et al ., 2008; Van Doornik et al ., 2008). It is unclear if there is an influence of paternal attributes on offspring quality to drive such processes, although female mate preference for large males has been observed in copper ( S. caurinus ) and quillback ( S. maliger ) rockfishes (Johansson et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some mammals, the female reproductive tract can recognize and interpret spermatozoon's genetic signature (Holt & Fazeli, 2015); nonetheless, it is unknown if rockfishes have the capability for distinguishing among sperm and for biased use of stored sperm. In some rockfishes ( Sebastes alutus , S. atrovirens , Sebastes caurinus , Sebastes maliger and S. schlegelii ), the distribution of fertilization success among males was observed to be skewed, which could point to potential post‐copulatory selection, disproportionate quantity of sperm from different males or study sampling effects (Gao et al ., 2017; Johansson et al ., 2012; Sogard, Gilbert‐Horvath, et al ., 2008; Van Doornik et al ., 2008). It is unclear if there is an influence of paternal attributes on offspring quality to drive such processes, although female mate preference for large males has been observed in copper ( S. caurinus ) and quillback ( S. maliger ) rockfishes (Johansson et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies employing genetic paternity analysis have demonstrated that rockfishes can be polyandrous (documented in at least 15 species to date), with as many as four sires per brood observed in studies of wild fishes and as many as six sires per brood observed in studies of captive fishes (Gao et al ., 2017; Gray et al ., 2015; Hyde et al ., 2008; Johansson et al ., 2012; Karageorge & Wilson Jr., 2017; Sogard, Gilbert‐Horvath, et al ., 2008; Van Doornik et al ., 2008). This may be a diversified bet‐hedging strategy when mate selection criteria are uncertain (Yasui, 1998, Hyde et al ., 2008, Sogard, Gilbert‐Horvath, et al ., 2008, Johansson et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling soon after spawning, for instance collecting eggs in nests, may limit the problem of selective mortality that cumulates through a cohort's life. Although such sampling can readily be done in experiment of captive spawning (Johansson et al, 2012;Whitcomb et al, 2014), logistic and ethical problems may constrain its feasibility in natural populations (but see Grimardias et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, rockfish are documented to have complex courting rituals (Helvey, 1982) and apparent mate choice (Johansson et al, 2012).…”
Section: The Widespread But Low Level Of Quillback Introgression Inmentioning
confidence: 99%